Pengalaman Hidup Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa Di RSD Mangusada: Life Experience of Chronic Kidney Failure Patients who Underwent Hemodialysis in Mangusada Regional Hospital - Putu Eva Cahyanti; Putu Wira Kusuma Putra; Gede Arya Bagus Arisudhana (Poltekkes Kemenkes Yogyakarta, 2021)
The Indonesian Renal Registry (IRR) notes that in 2015 a total of 30,554 patients who had chronic kidney disease with stage V had to undergo hemodialysis. Hemodialysis in patients with chronic kidney disease is one method to prevent death and extend life expectancy for people with chronic kidney disease. This study aimed to determine life experience of chronic kidney failure patients who underwent hemodialysis. This study used a phenomenological study design with sampling technique used purposive sampling. The results of research conducted can be identified and grouped with several themes, namely 1) early psychological responses diagnosed with chronic kidney failure, 2) physiological changes in the body, 3) family support during hemodialysis, 4) spiritual changes due to hemodialysis. This study can conclude that patients with chronic kidney failure who deny hemodialysis will replace changes in pshychological, physiological, and spiritual. Family support is very important to improve morale during hemodialysis repair. It is hoped that the research can become evidence based on the provision of services and care to patients with chronic kidney failure that underwent hemodialysis.